New practice or old tradition? EBBE's translation strategy of the Platform Sutra of the Sixth Patriarch from the perspective of Lefevere's theory of translation as rewriting - Wang, Hairuo (Frontiers in Communication, 2025)
Translation plays a crucial role in the global communication and dissemination of Buddhism, and English Base for Buddhist Exchange (EBBE)'s recent translation of the Platform Sutra of the Six Patriarch was a new contribution to the existing versions. This paper adopts Lefevere's theoretical perspectives to address the following research questions: (1) Has EBBE's translation of the Platform Sutra of the Sixth Patriarch fulfilled its stated translation philosophy? If so, how? (2) What are the potential communicative effects of the EBBE's version? (3) What are some problems in this translation to be addressed in the future? This paper used stratified sampling of three main narrative types across five different versions of the translation of the Platform Sutra, namely EBBE, Shi Chengguan, Huang Maolin, the Buddhist Text Translation Society, and John McRae, and compare them in terms of terminology translation, appraisal resources, thematic progression and Flesch Reading Ease. It is found that EBBE's version does stand out in readability and accessibility in the examined aspects, though certain improvement may still be possible. And an analysis based on Lefevere's theory was conducted for an understanding of the translation philosophy adopted in this latest translation.